Effect of commercially available bioaugmentors on the removal of ammonia and sulphide from brackishwater - Joseph, K O; Muralidhar, M; Gupta, B P; Krishnani, K K (Indian Journal of Fisheries, 2011)
The levels of amonnia and sulphide, when exceeded the critical limit becametoxic to aquatic life in brackishwater systems. An experiment was conducted inlaboratory to test the efficiency of commercially available materials viz. healthstone, BN-10 and zeolite powder in removing ammonia and sulphide frombrackishwater. Health stone + BN-10 combination was significantly (P